Efficacy of modified Child-Turcotte-Pugh score in predicting short-term mortality in spontaneous bacterial peritonitis - Ramu Muraleedharanpillai; Deni Joseph; Sandesh Kolassery; Saji Sebastian; Nithya Valsalamma; Gaurav Khatana; Lal Krishna Unnikrishnan; Gino Rony Philip (Egyptian Liver Journal)
Abstract Background and aims Spontaneous bacterial peritonitis (SBP) represents a critical complication of cirrhosis, characterized by a notably high mortality rate. Our study aimed to compare the predictive ability of several scores, including the model for end-stage liver disease (MELD) score, MELD sodium score (MELD-Na), MELD 3.0 score, Child-Turcotte-Pugh (CTP) score, and creatinine-modified CTP score (CrCTP), for in-hospital and 90-day mortality in patients with SBP. We also assessed the prognostic factors associated with in-hospital mortality and 90-day mortality. Methods This prospective observational study was carried out at the Government Medical College Kottayam from May 2023 to May 2024. Patients admitted with SBP were followed up for 3 months. During this time, demographic and biochemical data were collected. We used the receiver operating characteristics (ROC) curve, area under ROC curve (AUROC), and DeLong test to compare these scores. Results Of the 117 patients admitted for spontaneous bacterial peritonitis (SBP), 25 (21%) did not survive during their hospital stay, and 40 (34%) did not survive for 3 months. Multivariate logistic regression analysis revealed that serum creatinine level and all prognostic scores were significant predictors of mortality (p < 0.05). We observed that the MELD score (AUROC 0.813) and MELD 3.0 (AUROC 0.807) had better performance in predicting in-hospital mortality than the Child-Turcotte-Pugh (CrCTP) score (AUROC 0.783), while MELD 3.0 score (AUROC 0.816) and CrCTP score (AUROC 0.804) had better performance in predicting 3-month mortality than other scores. However, the superiority was not significant according to the DeLong test, which compares the different ROC curves. Conclusions The creatinine-modified CTP score was found to be a superior bedside score for short-term mortality prediction compared to the CTP score, and its accuracy was similar to that of the more recent MELD scores. Renal dysfunction is a crucial prognostic factor for both in-hospital and 90-day mortality.